Glossopharyngeal Neuralgia: A Comprehensive Update - Shamimul Hasan1 , Rajat Panigrahi2 , Sk. Tarique Ajiz3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Glossopharyngeal neuralgia (GN) is an unusualclinical condition where severe paroxysmal pain of theglossopharyngeal nerve. GN pain should be differentiated from trigeminal neuralgia pain, as the two neuralgiasshare several similar features. Thorough medical history coupled with a detailed clinical examination andhematologic and radiographic investigations is necessary for early and accurate diagnosis. Anticonvulsantsform the cornerstone of the medical management, and surgical interventions (microvascular decompressionand gamma knife surgery) is needed in cases resistant to pharmacotherapy.